Confronting Policy Challenges of the Great Recession - Alvi, Eskander (W.E. Upjohn Institute, 2023)
This book presents several notable economists who describe the perils the economy faced during the Great Recession and the policies—some successful, others not so much—that were implemented and why. By now, economists have had nearly a decade to examine the causes and consequences of the damage wrought by the Great Recession, and to assess the ensuing efforts to right the economy. The unprecedented losses, which spread across the global economy, posed extraordinary challenges for central bankers and policymakers alike, who were forced to throw out the playbook and create new, untested means for restoring growth.